Developing and evaluating the effectiveness of mobile phone-based career intervention for career competencies of Malaysian public managers: protocol for a mixed method study - Ho, Hsin Hung; Mohd Rasdi, Roziah; Ibrahim, Rahinah; Md Khambari, Mas Nida (Elsevier, 2020)
Background: This study presents a protocol for a mixed method study on the development and evaluation of the effectiveness of mobile phone-based intervention for enhancing career competencies of managers in the Malaysian public service. Career competencies, being central to the self-management and development of one's career, are necessary for proactive management of careers; they help to guide the individuals towards subjective career success which subsequently leads to organization success. However, there is a lack of career competencies intervention practices in the Malaysian public service. Therefore, this study aims to develop and evaluate the effectiveness of a user and expert centric mobile phone-based career intervention program of career competencies among Malaysian public managers. In this study, the Social Cognitive Career Theory (SCCT) is adopted as the framework to develop mobile phone-based intervention for career competencies. Method: This is a sequential exploratory mixed method study which involves, in Phase 1, a qualitative approach: reviewing of literature and interviewing experts and public servants who are users of mobile phones so as to obtain their perspectives regarding the components in the career intervention module and mobile phone application features. A quantitative approach is implemented in Phase 2 that evaluates the mobile phone-based career intervention program. Validation will be conducted to meet the objectives of (i) the usability of the mobile communication career intervention application (survey), and (ii) evaluation of the effectiveness of the intervention program for career competencies delivered through mobile phone application (randomized controlled trial). The career intervention program consists of five modules through which development is based on reflective, communicative and behavioral dimensions. Outcome: The primary outcome of this study is career competencies. The career competencies score will be compared between participants in the intervention and control group at the baseline, and follow-ups at week four and week 12 respectively, using mixed design ANOVA. Discussion: The results from this study will indicate the effectiveness of the career intervention program for career competencies in the reformation of public services management. The intervention can serve as a new modality to enhance career competencies among public managers in Malaysia if its effectiveness is proven.